196k views
2 votes
Make 'm' the subject of the formula'k=3m-2

User Tiagodws
by
5.1k points

2 Answers

3 votes

Answer:


m = (k + 2)/(3)

Explanation:


k = 3m - 2 \\ 3m = k + 2 \\ m = (k + 2)/(3)

User LoneWolfPR
by
5.3k points
4 votes

Answer:

m=(k+2)/3

Explanation:

k=3m-2

Make 3m the subject,

That will make -2 jump the equality sign to the other side, and then it turns to +2

k+2=3m

Divide both sides by 3

3m/3=(k+2)/3

m=(k+2)/3

User Sande
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.